2019
DOI: 10.3390/jcm8050720
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Metabolomic Approach Tracks Potential Serum Biomarkers of Disease Progression in Patients with Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by chronic hyperglycemia associated with alterations in carbohydrate, lipid, and protein metabolism. The prognosis of T2DM patients is highly dependent on the development of complications, and therefore the identification of biomarkers of T2DM progression, with minimally invasive techniques, is a huge need. In the present study, we applied a 1H-Nuclear Magnetic Resonance (1H-NMR)-based metabolomic approach coupled with multivariate data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 69 publications
4
45
0
Order By: Relevance
“…Metabolic abnormality has long been considered to be involved in a lot of diseases, such as neurodegenerative diseases including PD (Shao and Le, 2019) and Alzheimer' disease (Van Bulck et al, 2019), diabetes mellitus (Del Coco et al, 2019), chronic obstructive pulmonary disease (Lamonaca et al, 2017). 1 H-NMR based metabolomics has proven to be a key for the characterization of metabolic profiles relevant to brain function and disease (Ivanisevic and Siuzdak, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic abnormality has long been considered to be involved in a lot of diseases, such as neurodegenerative diseases including PD (Shao and Le, 2019) and Alzheimer' disease (Van Bulck et al, 2019), diabetes mellitus (Del Coco et al, 2019), chronic obstructive pulmonary disease (Lamonaca et al, 2017). 1 H-NMR based metabolomics has proven to be a key for the characterization of metabolic profiles relevant to brain function and disease (Ivanisevic and Siuzdak, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The main purposes supporting these contributions are to broaden the understanding on the metabolic environment of individuals in these different conditions, as well as potential molecular targets that link them all (Newgard, 2017). Studies have already shown the relationship between cardiometabolic diseases, obesity and diabetes with disturbances in the amino acid pathways such as aromatics and branched-chain amino acids (BCAA) (Newgard, 2017;Rauschert et al, 2017;Zhong et al, 2017;Libert et al, 2018;Del Coco et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Representative proton Carr-Purcell-Meiboom-Gill nuclear magnetic resonance ( 1 H CPMG NMR) spectra obtained from serum patients in the EAR and ADV HCC stages are shown in Figure 1. 2D NMR (J-resolved, homonuclear correlation spectroscopy (COSY), heteronuclear single-quantum correlation spectroscopy (HSQC), and heteronuclear multiple bond correlation spectroscopy (HMBC)) experiments were used to accurately assign the resonances of the identified metabolites, according to literature data and public databases [8][9][10][11]. The 1 H-NMR spectra were dominated by high-intensity signals ascribable to the sugar moieties of α and β-glucose, lactate and some high molecular weight metabolites, such as lipoproteins (VLDL/LDL).…”
Section: H-nmr Analysis Of Serum Samplesmentioning
confidence: 99%
“…Serum samples (200 µL) were processed according to standard procedures for NMR metabolomics measurement [8,9,54]. Briefly, prior to NMR analysis, sera were thawed at room temperature, and an aliquot of 200 µL was added of 400 µL of saline buffer solution (NaCl 0.9%, 50 mM sodium phosphate buffer in D 2 O containing TSP 0.05% wt for chemical shift calibration, pH 7.4) to minimize the variation in pH and transferred in a 5 mm NMR tube [54][55][56].…”
Section: Sample Preparation and Nmr Measurementsmentioning
confidence: 99%
See 1 more Smart Citation